The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1108/jrim-05-2016-0054
|View full text |Cite
|
Sign up to set email alerts
|

Impulse buying tendencies among online shoppers in Sweden

Abstract: Purpose The purpose of this study is to characterize consumers with high impulse buying tendency (IBT) by comparing them with low-IBT consumers in an online shopping context. Design/methodology/approach Data were collected through a postal survey to a random sample of Swedish citizens, resulting in 144 responses, which were analysed statistically.. Findings Results indicate that high-IBT consumers, compared to those with low IBT, are on average younger, more likely to be female and more frequent online sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 61 publications
2
31
0
1
Order By: Relevance
“…The proposed framework extends the literature in several areas. First, the current literature fails to provide a holistic picture of impulse buying (Ek Styvén et al, 2017;Xiao & Nicholson, 2013). This failure can be attributed to the fact that the literature has not conceptualized impulse buying as a process and outcome, which has resulted in some contradictory findings (Xiao & Nicholson, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed framework extends the literature in several areas. First, the current literature fails to provide a holistic picture of impulse buying (Ek Styvén et al, 2017;Xiao & Nicholson, 2013). This failure can be attributed to the fact that the literature has not conceptualized impulse buying as a process and outcome, which has resulted in some contradictory findings (Xiao & Nicholson, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been estimated that 90% of people purchase on impulse at least occasionally (Hausman, 2000). In this regard, past research has shown that impulse purchases generate a substantial proportion of retail industry sales (Ek Styvén, Foster, & Wallström, 2017;Kacen, Hess, & Walker, 2012) and even airport purchases (Geuens, Vantomme, & Brengman, 2004). Recent industry research also supported the fact that impulse buying accounts for a sizable percentage of all purchases (Amos, Holmes, & Keneson, 2014).…”
Section: Impulse Buyingmentioning
confidence: 99%
See 1 more Smart Citation
“…These positive emotions are found to be strongly correlated with impulse buying tendency (e.g. Kim and Eastin, 2011;Styvén, Foster, and Wallström, 2017). In addition, they further guide, and influence consumers urges to buy impulsively (e.g.…”
Section: Introductionmentioning
confidence: 90%
“…Конкретна марка у оваквим ситуацијама постаје избор потрошача тек у продајном објекту. Према резултатима бројних истраживања непланиране куповине последњих деценија имају доминантан удео у укупној продаји предузећа (Ek Styvén et al, 2017;Kacen et al, 2012). Таква ситуација је резултат интензивних улагања у маркетинг активности којима су потрошачи изложени и мотивисани на такву врсту куповине.…”
Section: преглед литературеunclassified